PELATIHAN PENINGKATAN KOMPETENSI GURU DALAM MENINGKATKAN MUTU PEMBELAJARAN BERBASIS ICT PADA SMP NEGERI 1 MUARO JAMBI - Yantoro Yantoro; Ali Idrus (Pusat Pengabdian Masyarakat (PPM) Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam Negeri (IAIN) Metro, 2021)
The presence of Information and Communication Technology (ICT) in learning is a challenge in itself for the world of education, in particular, learning technology today. Demands in responding to the globalization of education have appeared before our eyes. Various computer devices and their connections can deliver students to learn quickly and accurately if used correctly and appropriately. Therefore, it requires human resources who are responsive to ICT developments Learning will be more fun if the teacher is able to make ICT-based teaching materials that can increase student creativity. With the use of ICT-based teaching materials in learning, the learning process will be more interesting and can make students more contextual. If we observe carefully, until now teachers have not been able to develop ICT-based learning. In the learning process, the teacher still uses the old method, namely teacher-centered learning, so that students are less able to develop their creativity. This condition is also found in teachers at SMP N 1 Muaro Jambi. Where some teachers have not been able to carry out the ICT-based learning process, especially in compiling and making teaching materials, so that the learning process is only traditional, namely by lecturing, a little question and answer. Through community service activities, it will help teachers improve their competence in mastery of ICT which is useful in the learning process.